2011
DOI: 10.1007/s10995-011-0927-1
|View full text |Cite
|
Sign up to set email alerts
|

Parental Weight (Mis)Perceptions: Factors Influencing Parents’ Ability to Correctly Categorise Their Child’s Weight Status

Abstract: This study investigates parents' ability to correctly classify their child's weight status. The influence of parent and child socio-demographic and lifestyle factors on parental misclassification of their child's weight status is explored. A representative sample of Irish children (aged 5-12 (n = 596) years, aged 13-17 years (n = 441)) and their parents (n = 1885) were recruited to participate in a national dietary survey. Parental perceptions of their child's weight and their own weight were measured. Anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
5
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 40 publications
5
50
5
12
Order By: Relevance
“…8 Souto et al 9 reported that up to 43% of mothers of 6-24 month old infants with a low socioeconomic level underestimated their children's weight status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Souto et al 9 reported that up to 43% of mothers of 6-24 month old infants with a low socioeconomic level underestimated their children's weight status.…”
Section: Discussionmentioning
confidence: 99%
“…8 A limitation of this study is that it did not specify whether mothers or fathers should complete the questionnaire, so it was not possible to establish differences in perception by parents' gender. In addition, this study sets a precedent regarding parents' perception of their overweight or obese preschool children in Mexico, given that, to date, it had not been described in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coded characteristics for normal-weight samples not shown, including those from Arcan et al, 17 Bikin et al, 95 Boa-Sorta et al, 96 Brann et al, 97 Hudson et al, 98 Jeffery et al, 99 and Muhammad et al 100 component based on residual variance). Effect sizes were calculated for subsets of studies grouped according to the categorical moderator of interest, and heterogeneity of the effect sizes (as indicated by Q and I 2 statistics 102 ) both within and between categories was tested.…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…With respect to risk perception it might be important to consider whether parents evaluate their children's weight status correctly in the first place. Research showed that between 50-80% of parents of overweight or obese children underestimate their children's weight status (Aljunaibi, Abdulle, & Nagelkerke, 2013;Etelson, Brand, Patrick, & Shirali, 2003;Hudson, McGloin, & McConnon, 2012;Lim & Wang, 2013;Lundahl, Kidwell, & Nelson, 2014). This misperception might hinder parents to take appropriate measures to ameliorate weight status and to prevent potential health problems associated with overweight.…”
Section: Introductionmentioning
confidence: 99%